Gender Differences and the Meaning of Life among People Living with HIV/AIDS: A Cross-Sectional Study - Wulandari, Yuanita; Nursalam, Nursalam; Insani, Ma’rifatin (International Journal of Psychosocial Rehabilitation, 2020)
Meaning of life is an important term for people living with Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome (HIV/AIDS). Meaning of life has a correlation with quality of life. However, inconsistent research results on the meaning of life based on gender were found. This study aimed to analyze the gender difference in reference to the meaning of life among people living with HIV/AIDS. A descriptive analytical comparative study conducted with a cross-sectional approach was used. People living with HIV/AIDS older than 17 years old who were mentally healthy were enrolled in the study. Snowball sampling was performed to recruit 133 respondents. There were 69 females and 64 males enrolled in this study. Meaning of life was assessed using 10 questions through a meaning of life questionnaire. The questionnaire validity was in the range 0.60 to 0.79 and the questionnaire reliability was in the range of 0.713 to 0.798. The Mann-Whitney test was used to analyze the gender difference in relation to meaning of life. The range in age was 17 to 55 years old (mean [SD] age: 35.2[8.4]). The majority of the respondents were married and lived together with their spouse (41%), had graduated from senior high school (64%), worked in a private institution/office (57%), had 1 – 3 years length of time pass since diagnosis (43%), and their monthly income was in the range of 1.800.000 – 3.000.000 Indonesian Rupiah (48%). There was a difference in meaning of life based on gender among the people living with HIV/AIDS in Surabaya (p: 0.03; mean in females: 60.01; mean in males: 74.53). This study, in summary, has discovered that men are more likely to find there to be a meaning of life compared to women. Health care providers should discuss and address the existence the gender difference among people living with HIV/AIDS.